Perilaku dan Keterampilan Kepemimpinan di PT.X: Pendekatan Kualitatif Eksploratif - Richa Nahdalaily Fathara; Bambang Hermanto; Pratami Wulan Tresna (Universitas Malahayati, 2022)
Leadership has become an important part of organizational development to achieve a sustainable competitive advantage in responding to an increasingly uncertain business environment. Therefore, it is important to identify which specific behaviours and skills a leader must possess to achieve success in business. Without defining the required leadership behaviours and skills, companies may fail to optimize their leadership outcomes. The purpose of this study was to explore the types of leadership behaviours and skills adopted by PT.X operating in Pekanbaru, Riau and their goals in adopting these skills. It aims to determine the essential skills for entrepreneurial leadership in achieving success. The focus of this research specifically focuses on leadership at PT.X which is engaged in the culinary business sector in Pekanbaru. This research identifies nine skill categories which are the behaviours and skills possessed by leaders in this sector.